If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 35 = d + -12 Reorder the terms: 35 = -12 + d Solving 35 = -12 + d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-1d' to each side of the equation. 35 + -1d = -12 + d + -1d Combine like terms: d + -1d = 0 35 + -1d = -12 + 0 35 + -1d = -12 Add '-35' to each side of the equation. 35 + -35 + -1d = -12 + -35 Combine like terms: 35 + -35 = 0 0 + -1d = -12 + -35 -1d = -12 + -35 Combine like terms: -12 + -35 = -47 -1d = -47 Divide each side by '-1'. d = 47 Simplifying d = 47
| 9=10r-16r+5r | | -18=-61+d | | -9v+2v=-7+14 | | -10+6m=2(5+5m) | | p=6s | | 2a-36-2c+5a-7c+8b= | | 10(x+4)=7(x-3) | | 15=t+8 | | 1-(m-1)=2(m-3) | | 19-7=2x+x | | 9y+3x=27 | | t-72=-44 | | e+5(e+1)=4(2e-2)+11e | | 5y-2y=12+14 | | 10x-7=2x+29 | | 32x=3x^2+90 | | -7(n+5)=-32-6n | | 1-1(m-1)=2(m-3) | | 4x+15+6=3x-14 | | 4b^2-12b+9=0 | | -(6c-5)=4(7c-8)+3 | | 18+z=34 | | 3-2x=5x+9-2x-15 | | 5(g-2)+g=6(g-4) | | 7x+25=y | | -8+5x=x-56 | | -11d=81+16d | | 5x+2=3x-8 | | 7(k+3)=45-3(12-k) | | 6(4x-1)=3(8x-2) | | m+1=2m+7 | | 10x+10=8(x+3) |